2013
DOI: 10.1128/genomea.00204-13
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Bacillus stratosphericus LAMA 585, Isolated from the Atlantic Deep Sea

Abstract: Bacillus stratosphericus LAMA 585 was isolated from the Mid-Atlantic-Ridge seafloor (5,500-m depth). This bacterium presents the capacity for cellulase, xylanase, and lipase production when growing aerobically in marine-broth media. Genes involved in the tolerance of oligotrophic and extreme conditions and prospection of biotechnological products were annotated in the draft genome (3.7 Mb).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Notably, B. altitudinis and B. stratosphericus were first isolated in the stratosphere at 41 km above the earth’s surface and reported by (81). In contrast, Lima et al, 2013 (82) reported another B. stratosphericus strain LAMA 585 isolated in the Atlantic deep sea at 5,500 m depth. All these species of Bacillus are widely distributed on the earth, but instead of B. safensis, strains of B. altitudinis and B. stratosphericus were found most frequently in marine environments (80).…”
Section: Discussionmentioning
confidence: 94%
“…Notably, B. altitudinis and B. stratosphericus were first isolated in the stratosphere at 41 km above the earth’s surface and reported by (81). In contrast, Lima et al, 2013 (82) reported another B. stratosphericus strain LAMA 585 isolated in the Atlantic deep sea at 5,500 m depth. All these species of Bacillus are widely distributed on the earth, but instead of B. safensis, strains of B. altitudinis and B. stratosphericus were found most frequently in marine environments (80).…”
Section: Discussionmentioning
confidence: 94%
“…Bacillus stratosphericus is a Gram-positive endospore forming bacterium that belongs to phylum Firmicutes . It occupies quite distinct habitats, originally isolated from stratospheric air samples collected above 24 km of altitude and recently from the Mid-Atlantic-Ridge seafloor (5,500 m depth ( 1 , 2 ). In this study, Bacillus stratosphericus strain 5Co was isolated from medicinally important fruticose lichen Usnea florida that grows luxuriously in the central Florida region of the United States.…”
Section: Genome Announcementmentioning
confidence: 99%